Fiber-Enhanced Raman Gas Spectroscopy for 18O-13C-Labeling Experiments - Knebl, Andreas; Domes, Robert; Yan, Di; Popp, Juergen; Trumbore, Susan; Frosch, Torsten (Analytical Chemistry, 2019)
Stable isotopes are used in ecology to track and disentangle different processes and pathways. Especially for studies focused on the gas exchange of plants, sensing techniques that offer oxygen (O2) and carbon dioxide (CO2) sensitivity with isotopic discrimination are highly sought after. Addressing this challenge, fiber-enhanced Raman gas spectroscopy is introduced as a fast optical technique directly combining 13CO2 and 12CO2 as well as 18O2 and 16O2 measurements in one instrument. We demonstrate how a new type of optical hollow-core fiber, the so-called revolver fiber, is utilized for enhanced Raman gas sensing. Carbon dioxide and oxygen isotopologues were measured at concentrations expected when using 13C- and 18O-labeled gases in plant experiments. Limits of detection have been determined to be 25 ppm for CO2 and 150 ppm for O2. The combination of measurements with different integration times allows the creation of highly resolved broadband spectra. With the help of calculations based on density functional theory, the line at 1512 cm-1 occurring in the oxygen spectrum is assigned to 18O16O. The relative abundances of the isotopologues 18O16O and nitrogen 15N14N were in good agreement with typical values. For CO2, fiber-enhanced Raman spectra show the Fermi diad and hotbands of 12C16O2, 13C16O2, and 12C18O16O. Several weak lines were observed, and the line at 1426 cm-1 was identified as originating from the (0 4 0 2) → (0 2 0 2) transition of 12C16O2. With the demonstrated sensitivity and discriminatory power, fiber-enhanced Raman spectroscopy is a possible alternative means to investigate plant metabolism, directly combining 13CO2 and 12CO2 measurements with 18O2 and 16O2 measurements in one instrument. The presented method thus has large potential for basic analytical investigations as well as for applications in the environmental sciences.
CRIS-Team Scopus Importer:2023-04-20